Art education as experience, experimentation, communication and documentation: a research path in Italy in early childhood education/ educational services - Franca Giuliana Zuccoli (Universidade Federal de Santa Catarina, 2017)
This paper wants to reflect on the role of art education in the Italian educational contexts, particularly referring to the proposals designed for younger children. Starting from a quick overview of the evolution of the part of art education in the elementary school (6-10 years) programs designed to understand the underlying educational thinking, the contribution tries to analyze three issues that are currently relevant. The first linked to the connection with the world of contemporary art, with its political reach of communication; the second that analyzes the importance of laboratory experience, in terms of space layout and material predisposition, with its experimental possibilities; the third one focuses on the potential of documentation as a form of metacognitive reflection for both children and adults, educators, service providers, and parents.